PERANAN BUDAYA DALAM IMPLEMENTASI GOOD CORPORATE GOVERNANCE - CHAIRUMAN ARMIA (Jurnal Bisnis dan Akuntansi, 2002)
This paper uses Hofstede's (1991) organizational cultural dimension to analyze the implementation of good corporate governance. This paper descriptitively examines the research opportunity about the relationship between organization culture, behavior, and good corporate governance